Modulation of the CD200/CD200R Axis by IFN-β Treatment in a Mouse Model of Experimental Autoimmune Encephalomyelitis - Haghmorad, Dariush; Rahimmi, Arman; Pazoki, Alireza; Namazi, Fatemeh; Rahmani, Mohammad Reza; Amini, Abbas Ali (Iranian journal of immunology, 2025)
Interferon-b (IFN-β), a glycoprotein released during viral infections, plays a crucial role in modulating T cells involved in multiple sclerosis (MS). CD200 is an immunomodulatory molecule expressed in many cell types, including neurons. It reduces the progression of MS and experimental autoimmune encephalomyelitis (EAE) by interacting with CD200R, mainly expressed on myeloid lineage cells. This interaction prevents brain damage and slows the progression of the disease. This study investigated changes in the expression of CD200 and CD200R genes in the brains of mice induced with EAE. Female C57B/L6 mice were divided into three distinct groups: 1) EAE-induced and treated with IFN-b, 2) EAE-induced and treated with phosphate-buffered saline (PBS), and 3) a healthy control group. Two weeks after treatment, the mice were euthanized, and whole-brain tissues were used for mRNA extraction. After cDNA synthesis, the expression of CD200 and CD200R genes was evaluated using Taqman Real-Time PCR. Leukocyte infiltration and demyelination were assessed using Hematoxylin and Eosin staining (H&E) as well as Luxol fast blue (LFB). IFN-β treatment significantly reduced disease progression and demyelination. Furthermore, mice treated with IFN-β showed improved weight gain. The findings also indicated no notable change in CD200 gene expression across the groups examined. However, the expression of CD200R decreased in the IFN-β-treated group, but significantly increased in the untreated group. Our findings suggest that IFN-β treatment may decrease CD200R expression by reducing inflammation. Additionally, the elevated expression in the untreated group may explain why EAE is self-limiting.